PMO-025 Three-year review of local hepato-pancreatobiliary (HPB) cancer service & its impact on cancer detection in a non-tertiary centre in Mersey Region. (28th May 2012) - Clark, K; Boon, A; Faizallah, R; Singhal, A
Abstract : Introduction: Patients with HPB cancer pose complex clinical problems requiring close liaison between primary, secondary & tertiary care. Reconfiguration of cancer services in the Mersey region has lead to standardisation of care for HPB cancer patients via referral to Regional Specialist Centres (RSC). However local cancer care remained fragmented and limited by the variable expertise of the respective clinical teams involved. Therefore we developed a local HPB Cancer Service (HPBCS) and hereby report 3-year impact of this service on overall patient care and cancer detection rates outside tertiary referral centres. Methods: The HPBCS was launched on the Wirral in June 2008, the first such service in a large district general hospital (catchment population of 360 000) in the Mersey region. All patients with suspected HPB cancer were referred to the local HPB Team comprising of two HPB consultants and a specialist nurse. Patients are identified via 2-week referrals from primary care, acute admissions, ward referrals and radiology flags—a new concept that year upon year provides a valuable resource to the service. All patients are managed as per the Mersey & Cheshire Cancer Network protocol with discussion at the appropriate RSC MDT meetings. The team meets weekly to discuss all new referrals, MDT outcomes and any sick patients. In addition to the consultant clinics, there is weekly HPB nurse-led outpatient & telephone clinics that provides urgent feedback of tertiary MDT decisions, rapid access for symptom control and ensures continuity of care. Results: There is a sharp increase in the HPB cancer detection and referral rates since establishing the local HPBCS which has sustained over 3-year period as summarised in Abstract PMO-025 table 1 . Conclusion: Since commencement of local HPBCS, there is sustained increase in number of suspected HPB cancers identified within the trust. These are referred on to the regional MDTs within 2 weeks, leading to timely and uniform care as per regional network guidelines with local ownership of care. Service was formally praised in MCCN peer review in 2010 and awarded Wirral Trust Foundation Award in 2011. There is small but consistent rise in detection of liver lesions which may reflect increasing incidence of chronic liver diseases nationally. Ever increasing pool of surveillance patients & radiology alerts contribute to significant ongoing work load. Competing interests: None declared.